A Review of Primary Malignant Cutaneous Soft Tissue Tumors Seen in a Tertiary Institution - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Introduction:The baseline data of primary malignant cutaneous soft tissue tumors in this environment had been determined. It is important that as the years roll by, data collection and analyses are indispensable to determine the current trend of this tumor on one hand and compare it with the baseline data from previous studies on the other hand. The aim of this study is therefore to determine the frequency and the histopathological types of primary malignant cutaneous soft tissue tumors at the University of Benin Teaching Hospital (UBTH), Benin City, Edo State, Nigeria.Methodology:This was a retrospective study of all primary malignant cutaneous soft tissue tumors that were histologically diagnosed from 1stof January 2004 to 31stof December 2013 in the Department of Morbid Anatomy, UBTH. Data were obtained from departmental archives. Data analysis was done using the SPSS statistical package version 16 (V.16.0).Results:A total of 187 malignant cutaneous tumors were diagnosed over the study period, and 87 (46.52%) of these cases were primary malignant cutaneous soft tissue tumors. Their mean age was in the fourth decade of life. Females were slightly more affected with a male:female ratio of 1:1.2. The histopathological types were angiosarcomas (2.3%), dermatofibrosarcoma protuberance (10.3%), and Kaposi’s sarcoma (87.4%) in increasing order of frequency.Conclusion:The earlier determined reference point data of primary cutaneous soft tissue tumors in our environment were updated to include cutaneous angiosarcoma, thus bringing this rare tumor to the attention of both the pathologist and dermatologist. An increase in the frequency of dermatofibrosarcoma protuberance and Kaposi’s sarcoma was also noted.